Sarcoid-like reaction in patients with malignant tumors: Long-term clinical course and outcomes - Huh, Jin-Young; Moon, Do Sik; Song, Jin Woo (Frontiers in Medicine, 2022)
Background: The development of non-caseating epithelioid cell granulomas in cancer patients who do not fulfill the systemic sarcoidosis criteria is termed sarcoid-like reaction (SLR). Little is known about this condition’s natural course and impact on the prognosis of malignancy. We aimed to investigate the natural course and prognostic value of cancer-associated SLR. Methods: Clinical data were retrospectively analyzed in 32 patients with biopsy-proven cancer-associated SLR. Among patients with non-small cell lung cancer (NSCLC), SLR cases (n=8) were matched with non-SLR cases (n=78) for survival analysis. Results: Among the included patients, the mean age was 59.7 years, and 70.6% were female. The median follow-up period was 35.6 months (interquartile range [IQR]: 14.0–61.4 months). Of all the included malignancies (n=32), breast cancer (25.0%) and NSCLC (25.0%) were the most common, with stage I being the most frequent tumor stage (59.4%). During follow-up, SLR progression to overt sarcoidosis was not observed. In the 28 patients with available follow-up computed tomography images (median interval: 24.9 months; IQR: 14.4–41.7), 4 patients received corticosteroids (n=4), resulting to a decrease of SLR lesions. Meanwhile, among those who did not receive treatment (n=24), the extent of SLR decreased or did not change in 85.7% of them, whereas 3.6% had increased SLR extent. Furthermore, among patients with NSCLC, SLR was not associated with overall survival (hazard ratio [HR] = 1.28, 95% confidence interval [CI]: 0.02–67.71, P=0.882) and recurrence of malignancy (HR = 1.27, 95% CI 0.21–7.51, P=0.793) in the Cox proportional hazard regression model. Conclusions: During the follow-up of cancer-related SLR, we found no further evidence for systemic sarcoidosis, and most of the lesions decreased or did not change. Development of SLR was also not associated with overall survival or disease-free survival in patients with NSCLC.